Response of Vitis vinifera L. cv. Barlinka/Ramsey to Soil Water Depletion Levels with Particular Reference to Trunk Growth Parameters - Myburgh, P.A. (South African Journal of Enology and Viticulture, 2017)
Vitis vinif era L. cv Barlinka/Ramsey was irrigated with micro sprinklers at 10  % , 40 % and 60 % depletion of plant available water (PAW) in a field trial on a sandy soil in the Hex River Valley. A fourth treatment was trickle-irrigated at 40% PAW depletion.  Irrigations were scheduled with tensiometers. A system which measures trunk diameter was used for automatic trickle irrigation of a fifth treatment. Measuring trunk growth continuously using linear variable differential transformers revealed no increase in diameter between budbreak and bloom. From bloom until veraison trunk diameter increased, whereafter it decreased slightly.  Average seasonal trunk diameter increases were 0,8 mm, 1,2 mm and 2,1 mm, for the 60%, 40% and 10% PAW depletion levels, respectively. When well supplied with water, diurnal trunk contraction ranged between 0 mm and 0,01 mm per day. As water stress increased, trunk contraction increased curvilinearly to a maximum value of ca 0,1 mm per day. The most acceptable combination of growth, yield, berry size and eating quality was obtained by irrigation using micro sprinklers at 40% PAW depletion.  Irrigation at 10% as well as 60% PAW depletion reduced berry taste and colour significantly. Root studies by means of the profile wall method showed that irrigation at 10 % PAW depletion limited fine root development in comparison to 40 % PAW depletion.  Trickle irrigation stimulated development of fine roots within 500 mm of the grapevine as opposed to micro sprinklers. Trickle irrigation at 40% PAW depletion tended to increase water stress in comparison to micro sprinklers. This tended to improve grape quality, but reduced production and berry size. Although automatic irrigation held no significant advantages regarding yield and quality in comparison to manual scheduling with the aid of tensiometers, it did simplify irrigation management.